Investigating microbial indicators of anthropogenic marine pollution by 16S and 18S High-Throughput Sequencing (HTS) library analysis. Issue 14 (16th August 2019) - Buccheri, Maria Antonietta; Salvo, Eliana; Coci, Manuela; Quero, Grazia M; Zoccarato, Luca; Privitera, Vittorio; Rappazzo, Giancarlo
ABSTRACT: High-Throughput Sequencing technologies are providing unprecedented inventories of microbial communities in aquatic samples, offering an invaluable tool to estimate the impact of anthropogenic pressure on marine communities. In this case study, the Mediterranean touristic site of Aci Castello (Italy) was investigated by High-Throughput Sequencing of 16S and 18S rRNA genes. The sampling area falls within a Marine Protected Area and, notwithstanding, features an untreated urban wastewater discharge. Seawater samples were collected close to the wastewater output (COL) and at a second station about 400 m further off (PAN), before and after a summer increase in population. Prokaryotic communities clustered according to stations, rather than to seasons. While PAN showed a typical, not impacted, marine microbial composition, COL was consistently enriched in Epsilonproteobacteria and Firmicutes. Protist communities showed a peculiar clustering, as COL at springtime stood alone and was dominated by Ciliophora, while the other samples were enriched in Dinophyta. Analysis of alternative, detectable by High-Throughput Sequencing, microbial indicators, including both faecal- and sewage-associated, allowed uncovering the different sources of pollution in coastal and anthropogenically impacted marine ecosystems, underpinning the relevance of High-Throughput Sequencing-based screening as rapid and precise method for water quality management. Abstract : The analysis of marine microbial communities, through High-Throughput Sequencing, allows identification of alternative indicators that unveils human activities impacting a marine protected area within the Mediterranean coastal sea.